Cationic terminal aminoborylene complexes: controlled stepwise insertion into M=B and B=N double bonds. - Pierce, G; Aldridge, S; Jones, C; Gans-Eichler, T; Stasch, A; Coombs, N; Willock, D (2007)
(Chemical Equation Presented) One thing leads to another: Reactions of the cationic BN vinylidene analogues 1-[BArF4] (R = Cy, iPr; ArF = 3,5-(CF3)2C6H3) towards dicyclohexylcarbodiimide proceed by unprecedented insertion chemistry for terminal borylene complexes. Controlled, stepwise insertion into the Fe=B and B=N bonds is demonstrated, sequentially forming four-membered rings linked at a spirocyclic boronium center. © 2007 Wiley-VCH Verlag GmbH and Co. KGaA.